USE OF HIGHER ORDER THINKING SKILLS (HOTS) TEACHING MATERIALS TO GROW READING LITERACY IN MADRASAH IBTIDAIYAH STUDENTS - Esty Cahyaningsih; Andi Prastowo (IJIET (International Journal of Indonesian Education and Teaching), 2025)
The reading literacy skills of students in Indonesia are generally still low. However, some schools are already able to have high student reading literacy. This research aims to reveal HOTS teaching materials as an effort to foster the reading literacy of Madrasah Ibtidaiyah students. The research location was carried out at one of the favorite private Madrasah Ibtidaiyah (MIS) located in East Jakarta. The research was conducted in the even semester of the 2023/2024 academic year. This research uses a qualitative approach with a case study design. Data collection was obtained through various sources consisting of interviews, observations, and documentation with research subjects, namely the school principal, curriculum coordinator teacher, and 47 class V students. All research data that has been collected is then analyzed using Miles, Huberman, and Saldana's interactive model data analysis techniques. This model includes data condensation, data presentation, and conclusion drawing. The implications of this research show that to foster reading literacy, teaching materials based on high-level thinking skills are needed.